The anatomy of desire eaudiobook A novel. - Dorn, L. R. (2021)
Audie Award finalist for Multi-Voice Performance! Performed docuseries style by a star-studded full cast including Santino Fontana, Shelby Young , Marin Ireland, JD Jackson, Dan Bittner, Vikas Adam, Gabra Zackman, Fred Berman, Darrell Dennis, Oliver Wyman, Jonathan Davis, Hilary Huber, and Lisa Flanagan For fans of riveting true crime docuseries a la Serial and Making a Murderer, The Anatomy of Desire is a modern tale of crime and punishment exploring unbridled ambition, blinding passion, and the dark side of desire Claire Griffith has it all, a thriving career, a gorgeous boyfriend, glamorous friends. She always knew she was destined for more than the life her conservative parents preached to her. Arriving in Los Angeles flat broke, she has risen to become a popular fitness coach and social media influencer. Having rebranded herself as Cleo Ray, she stands at the threshold of realizing her biggest dreams. One summer day, Cleo and a woman named Beck Alden set off in a canoe on a serene mountain lake. An hour later, Beck is found dead in the water and Cleo is missing. Authorities suspect foul play, and news of Cleo's involvement goes viral. Who was Beck? An infatuated follower? Were she and Cleo friends or lovers? Was Beck's death an accident . . . or murder? Told in the form of an immersive investigative docuseries, L. R. Dorn's brilliant reimagining of Theodore Dreiser's classic crime drama, An American Tragedy, captures the urgency and poignance of the original and rekindles it as a very contemporary and utterly mesmerizing page-turner.